Darwin's legacy : the status of evolutionary archaeology in Argentina - Cardillo, Marcelo,; Muscio, Hernán Juan, (South American archaeology series ;, 2016)
This text collects the contributions to the symposium 'The Current State of Evolutionary Archeology in Argentina' that was held in Buenos Aires, for celebrating the 200th anniversary of Charles Darwin's birth and the 150th anniversary of the publication of 'On the Origin of Species'.